Comparison of different antimicrobial sequences on nursery pig performance and economic return - M U Steidinger; D Dau; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2009)
A total of 1,008 weanling pigs (12.0 lb and 19 d of age) were used in a 42-d experiment to compare different antibiotic regimens on growth performance and economic return. From d 0 to 11 and d 11 to 21, pigs were fed diets containing no antibiotic, a combination of Denagard (Novartis Animal Health, Greensboro, NC) at 35 g/ton and chlortetracycline at 400 g/ton (Denagard/CTC), or Pulmotil (Elanco, Greenfield, IN; 363 g/ton from d 0 to 11 and 181 g/ton from d 11 to 21). From d 21 to 42, pigs previously fed Denagard/CTC or Pulmotil were fed diets containing no medication, Denagard/CTC, or a combination of Mecadox (Philbro Animal Health Corp., Ridgefield Park, NJ) at 25 g/ton and oxytetracycline at 400 g per ton (Mecadox/OTC). Adding Denagard/CTC or Pulmotil to the diet from d 0 to 11 and d 11 to 21 improved (P<0.01)ADG, ADFI, F/G, and income over feed cost (IOFC). There were no differences (P>0.21) in ADG or ADFI between pigs fed Denagard/CTC and pigs fed Pulmotil; however, pigs fed Denagard/CTC tended to have better (P<0.09) F/G from d 0 to 21. Feed cost was also lower (P<0.01) and IOFC was greater (P<0.03) from d 0 to 21 for pigs fed Denagard/CTC than for pigs fed Pulmotil. Adding Denagard/CTC or Mecadox/OTC to the diet from d 21 to 42 increased (P<0.05) ADG, ADFI, and IOFC compared with feeding no antibiotic, but there were no differences (P>0.17) in pig performance or IOFC between pigs fed Denagard/CTC and Mecadox/OTC. For the overall trial, adding antibiotics to the diet during any phase improved (P<0.05) ADG, ADFI, F/G, and IOFC. These results demonstrate that adding antibiotics to the nursery diet improved pig performance and economical return on this commercial farm.; Swine Day, Manhattan, KS, November 19, 2009
Keywords: Swine day; 2009; Kansas Agricultural Experiment Station contribution; no. 10-014-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1020; Antimicrobial; Swine